Pengaruh Budaya Terhadap Pendidikan Disiplin Militer di Indonesia - Zidni Husnurofik; Samsun Samsun; Awaluddin Tjalla; Iva Syarifah (Syntax Idea)
Military discipline education plays a crucial role in shaping the character and leadership of individuals in the military environment. Culture, as a powerful social factor, can exert significant influence on the military discipline education process. This article aims to explore the influence of culture on military discipline education through a literature review method. In the process, we present the results of analyses of various relevant studies that highlight the role of culture in shaping values, norms, and practices in military discipline education. The main findings of this research reveal that culture has a significant impact on the formation and implementation of military discipline education, including values, ethics, and the level of discipline applied in the military environment. These results provide deep insights into the importance of considering cultural factors in designing effective military discipline education programs. This knowledge can contribute to improving the quality of military discipline education, ultimately positively affecting the capabilities and professionalism of military personnel.